Difference between revisions of "2025 AIME II Problems/Problem 2"

(Solution 1)
m (Solution 1)
 
Line 25: Line 25:
 
Since <math>n</math> is positive, <math>n = 1</math>, <math>11</math> and <math>37</math>.
 
Since <math>n</math> is positive, <math>n = 1</math>, <math>11</math> and <math>37</math>.
  
<math>1 + 11 + 37 = \framebox{49}</math> is the correct answer
+
<math>1 + 11 + 37 = \framebox{049}</math> is the correct answer
  
 
~[https://artofproblemsolving.com/wiki/index.php/User:Tonyttian Tonyttian]
 
~[https://artofproblemsolving.com/wiki/index.php/User:Tonyttian Tonyttian]

Latest revision as of 13:05, 15 February 2025

Problem

Find the sum of all positive integers $n$ such that $n + 2$ divides the product $3(n + 3)(n^2 + 9)$.

Solution 1

$\frac{3(n+3)(n^{2}+9) }{n+2} \in Z$

$\Rightarrow \frac{3(n+2+1)(n^{2}+9) }{n+2} \in Z$

$\Rightarrow \frac{3(n+2)(n^{2}+9) +3(n^{2}+9)}{n+2} \in Z$

$\Rightarrow 3(n^{2}+9)+\frac{3(n^{2}+9)}{n+2} \in Z$

$\Rightarrow \frac{3(n^{2}-4+13)}{n+2} \in Z$

$\Rightarrow \frac{3(n+2)(n-2)+39}{n+2} \in Z$

$\Rightarrow 3(n-2)+\frac{39}{n+2} \in Z$

$\Rightarrow \frac{39}{n+2} \in Z$

Since $n + 2$ is positive, the positive factors of $39$ are $1$, $3$, $13$, and $39$.

Therefore, $n = -1$, $1$, $11$ and $37$.

Since $n$ is positive, $n = 1$, $11$ and $37$.

$1 + 11 + 37 = \framebox{049}$ is the correct answer

Tonyttian

~ Edited by aoum

See also

2025 AIME II (ProblemsAnswer KeyResources)
Preceded by
Problem 1
Followed by
Problem 3
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15
All AIME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png